Characteristics of Febrile Convulsions and The Association Between Ketonuria and Febrile Convulsions - Sh Mahmood , Najdat; Abood Khalil, Oday; Ibrahim Alezzi , Jalil (Diyala Journal of Medicine, 2021)
Background: Febrile seizures are common and mostly benign. There is growing evidence that ketone bodies derived from fatty acid oxidation during fasting or consumption of high-fat diets can exert broad neuroprotective effects, including anti-convulsant effects. Objective: To determine the characteristics of febrile convulsions and the relationship between ketonuria and febrile convulsions. Patients and Methods: A cross-sectional comparative study was done between May 2018 – December 2019 at Al-Batool teaching hospital. The data included 100 children aged between (6- 60 months) admitted to the emergency unit, 50 % of them were having a febrile convulsion, while the others were presented with fever without a seizure. Blood samples were measured for serum glucose and urine samples were taken for level of ketone bodies (KB) and analyzed by reagent strip test. Statistical analysis was done by using SPSS version 21, level of association between variables was tested by Chi-square at 0.05. Results: Febrile convulsions occur equally in males and females and more likely in children less than 18 months of age (P value=0.157). Causes of fever in children with febrile convulsion were mostly respiratory causes (p value=0. 000). The incidence of hypoglycemia and ketonuria were slightly more common in the non-convulsive group of the study to be statistically insignificant (p- values were 0.169 and 0.275, respectively). Conclusion: The febrile convulsions affect equally males and females and the major cause of fever was respiratory infections. There is no significant relationship between ketonuria and the occurrence of febrile convulsions.